Gender Power Dynamics: Male Marginalization in the Works of John Nkemngong Nkengasong - Lum, Mary Louisa; Labang, Oscar C. (Advances in Social Sciences Research Journal, 2023)
Contrary to the general tendency in critical literary circles which, since the rise of feminism and gender studies, has interrogated the female condition under the yoke of patriarchy, this paper examines the extent to which the female gender dominates and marginalizes the male gender (in patriarchal societies) thereby creating the necessity to (re)examine feminine power and the way it operates socially and sexually. Using ideas from Chinweizu (1990) as theoretical positions for the analysis of selected works by the Cameroonian scholar, novelist, playwright and poet, John Nkemngong Nkengasong, this paper investigates the power dynamics amongst female and male gender from two perspectives: the manipulation of male instinct and the exploitation of male inadequacies. It shows that in the selected works of Nkengsaong the females control power that formally belong men to the extent that power becomes not just a mechanism for getting what they want but also for making males to feel insignificant, irrelevant, and helpless.